Wild Seed Conservation in National Botanical Garden, Lalitpur, Nepal - Chaudhary, Tulasa; Nagarkoti, Manisha; Neupane, Sudhir; Lamichhane, Dipak; Pandey, Jeevan; Parmar, Gaurav (Journal of Plant Resources, 2022)
Seed banks are the important means for the ex-situ conservation of plant genetic diversity. Though the seeds of domesticated varieties have been preserved for a long time, wild seed conservation is a noble concept in Nepal. Seed Bank of National Botanical Garden, Godawari, Lalitpur (NBG) is a major initiative for the conservation of wild plant seeds in Nepal. In the present study, a standardized seed banking procedures practiced at the Seed Bank of NBG, from seed collection to storage including germination test has been included. Currently, seeds of 84 wild species belonging to 77 genera of 47 families are preserved in the NBG. Alongside preserving wild genetic resources, NBG Seed Bank also provides materials for restoration, reintroduction and research that supports broader plant conservation goals, as well as contributes to education and public awareness about plant conservation.